MUSLIM TRAVEL MOTIVATION IN HALAL TOURISM IN INDONESIA: A CASE STUDY ON CURRENT CONDITION OF DOMESTIC TOURIST IN BANDUNG - Addelina 29116040, Kerry
Islamic economics is an important part of today's global economy. There are seven sectors of Islamic economy that have increased significantly, such as culinary, Islamic finance, insurance industry, fashion, cosmetics, pharmacy, entertainment, and tourism. Sector of Islamic economy that has experienced significant growth in lifestyle product in tourism sector is Sharia Tourism or commonly called Halal Tourism. Halal tourism has become part of the national tourism industry to position Indonesia as a center for halal tourism in the world in the future. The number of foreign tourists visiting Indonesia in recent years is dominated by foreign tourists from ASEAN countries. Meanwhile, with the increasing number of sharia conscious consumers in Indonesia, there are now many domestic tourist demand guarantees of halalness and an Islamic atmosphere along their journey. Indonesian Muslim population is the right target for the Indonesian halal industry market. Therefore, it seems necessary to conduct the research to find out what kind of factors that motivate domestic tourists so that Indonesia as a halal destination can also reap markets in its own country. This research conducted with qualitative analysis using phenomenological study by did in-depth interviews and observation to find out what kind of factors and reasons lie behind tourist motivation to do halal tourism. This study found that there are various perceptions towards halal tourism in the society. This growing perception of what is halal tourism is less precise, thus influencing the motivation of the tourists. The biggest factor causing the misperception is lack of understanding and knowledge about halal tourism. There are also several other factors that affect one's motivation in doing halal tourism. This factor is divided into two namely the push and pull factor. Push factors in halal tourism include novelty and knowledge seeking, self-enhancement, and pleasure seeking. While factors included in the pull factor is travel arrangement & facilities, safety & cleanliness and event & cost. This study concludes that knowledge and information about halal term and halal tourism need to be given simultaneously to improve the understanding of the tourists and generate a positive perception in order to increase their motivation to do halal tourism.